The Effect of Calcium Hydroxide and Neem Products On Paddy During Storage - DESALE, TUSHAR VILASRAO; Genitha Immanuel, Minali Masih (Journal of Scientific Agriculture, 2018)
The evaluation of “Effect of Neem extract and Calcium Hydroxide (CaOH) on paddy during storage” was carried out seed processing plant, Sam Higginbottom University of Agriculture, Technology and Sciences, Allahabad. Different concentration of Neem and CaOH was taken for evaluation. Neem lime balls were prepared. These balls were made by mixture of CaOH and Neem leaf extract. Weight of each ball was 6 g. 12 kg of paddy were issued by Seed Research Farm SHUATS. Twelve different types of samples were prepared of 1 kg paddy in each gunny bag. The evaluation of moisture content was measured at interval of 5 days total evaluation period was 10 days. The result showed that the changes in moisture content, weight and seed viability percentage. The moisture content low decreases in controlled sample comparison to treated sample. The seed viability percentage was remaining constant for all 10 days in treated sample and some decrease in controlled sample. Hence the Neem and Calcium Hydroxide are very effective for post harvest management of paddy.